Effect of extract from ginseng rust rot on the inhibition of human hepatocellular carcinoma cells in vitro. (September 2019) - Hu, Jing; Jiao, Jie; Wang, Ying; Gao, Mingyan; Lu, Zhengcheng; Yang, Fan; Hu, Cuihua; Song, Zhengxun; Chen, Yujuan; Wang, Zuobin
Highlights: Toxic were examined in human liver cancer cells and human normal liver cells. Cells morphologies were analyzed by employing multiple methods. Ginseng rust rot epidermis shows enhanced anti-cancer activity and little toxicity. Anti-cancer action was ascribed to the collapse of the cellular membrane in cells. Abstract: Hepatocellular carcinoma (HCC) is one of major leading causes of cancer death worldwide. As a traditional medicine, the anti-cancer function of ginseng is being growingly recognized and investigated. However, the effect of ginseng rust rot on human HCC is unknown yet. In this study, the HCC cells were treated with different parts of mountain cultivated ginseng rust rot and compared with human normal liver cells. The morphology, survival rate and β -actin expression of the cells were changed by introducing the ginseng epidermis during the incubation process. Notably, the results reveal that the ginseng epidermis can induce apoptosis by altering the morphologies of cells, indicating the practical implication for the HCC treatment and drug development.